CarbonFiberStone: a new carbon negative and cost-effective alternative to conventional building materials by fusing three different CDR technologies - Friedrich J Bohn; Uwe Arnold; Ömer Bucak; Erik Frank; Leonie Schrafstetter; Kolja Kuse (Environmental Research Letters, 2025)
Unprecedented urbanization has led to a sharp increase in the world’s building stock, increasing material consumption and environmental impact. This study introduces CarbonFiberStone (CFS), a novel lightweight construction material, and assesses its carbon footprint in a specific building application. CFS is defined as a millimeter-thin bio-based carbon fiber fabric bonded to compression-resistant stone slabs using an adhesive. CFS is extremely resistant to compression and tension. The resulting stone powder from the stone cutting process is used for enhanced rock weathering. The wall element presented here incorporates a layer of biochar for insulation purposes. Using life cycle assessment and techno-economic analysis, we compare five CFS-based building blocks with two conventional reinforced concrete blocks in single and multi-story residential buildings. The results show that CFS walls achieve a net carbon negative balance of −56.86–65.32 kg CO _2eq m ^−2 , sequestering 0.10–0.15 t CO _2 per square meter of living space at similar costs to conventional construction with reinforced concrete. These results show that CFS has the potential to become a viable, sustainable alternative to conventional building materials and thus has the potential to make a significant contribution to the 1.5 °C target of the Paris Agreement.